MOOD AND BEHAVIORAL DISORDERS IN ALZHEIMER’S DISEASE: CURRENT ISSUES AND TREATMENT - Klaudia Drewko; Sylwia Kopeć; Karolina Bryła; Szymon Gruszka; Klaudia Kożuchowska; Dawid Pilarz (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: In recent years, the rise in population aging and longer life expectancy have led to a higher prevalence of Alzheimer’s disease (AD), making it the most widespread form of dementia globally. Despite, the disease being mainly associated with cognitive decline and severe memory loss, there are many behavioral and psychological symptoms of Alzheimer’s disease that prevent independent functioning. This introduction highlights the significance of understanding neuropsychiatric symptoms that appear in individuals with Alzheimer’s disease which can be very diverse.Brief description of the state of knowledge: Patients with Alzheimer’s disease suffer from a broad spectrum of neuropsychiatric symptoms including depression, aggression, apathy, delusions/hallucinations, abnormal motor behavior,  unusual activities, eating disorders, changes in biological rhythms, and sexual dysfunctions. The majority of these symptoms appear in over half of the patients with Alzheimer’s disease, posing a serious concern that often leads to hospitalization. Despite the considerable social impact, treatment approaches for these symptoms remain poorly defined. Additionally, the presentation and severity of these symptoms can vary depending on the patient’s gender and age of onset.Summary: In summary, the aim of this review is to outline and highlight the latest knowledge on neuropsychiatric disorders, which occur in patients suffering from Alzheimer’s disease, focusing mainly on mood and behavioral symptoms.  These symptoms can be classified into various categories based on specific criteria, but what matters most is accurately identifying the disease’s signs, as they can sometimes appear before the more typical symptoms of Alzheimer’s disease.